2022
DOI: 10.1007/s13593-022-00850-z
|View full text |Cite
|
Sign up to set email alerts
|

Diversification improves the performance of cereals in European cropping systems

Abstract: In the face of climate change, cropping systems need to achieve a high performance, providing food and feed and adapting to variable environmental conditions. Diversification of cropping systems can support ecosystem services and associated biodiversity, but there is little evidence on which temporal field arrangement affects the performance of crop yields (productivity and stability), partly due to a lack of long-term data and appropriate indicators. The objectives of this study were to quantify the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 30 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…It is well documented that the inclusion of either legume or brassica break crops in cropping sequences can enhance subsequent wheat yields; especially where soil N availability and/or disease are constraints to productivity (Kirkegaard et al 2008;Angus et al 2015;Ladha et al 2022;Reckling et al 2022;Zhao et al 2022). However, the on-farm studies reported here indicated that broadleaf break crops can also contribute to increased grain yields by facilitating the reduction of ARG weed pressure.…”
Section: Discussionmentioning
confidence: 61%
“…It is well documented that the inclusion of either legume or brassica break crops in cropping sequences can enhance subsequent wheat yields; especially where soil N availability and/or disease are constraints to productivity (Kirkegaard et al 2008;Angus et al 2015;Ladha et al 2022;Reckling et al 2022;Zhao et al 2022). However, the on-farm studies reported here indicated that broadleaf break crops can also contribute to increased grain yields by facilitating the reduction of ARG weed pressure.…”
Section: Discussionmentioning
confidence: 61%
“…Bradyrhizobium ) needs to be improved, especially under cool weather conditions (Halwani et al, 2021; Kühling et al, 2018; Zimmer et al, 2016), (iii) farmers need to have the knowledge and markets to sell crops within their region at attractive prices and (iv) human diets need to change to reduce the demand for soybean‐based feed for ruminants. Second, climate change adaptation and low‐pesticide strategies promote diversification of the cropping system (Reckling et al, 2022) as an important pillar, and soybean—as a nitrogen‐fixing legume—offers a range of environmental benefits that have already increased the crop's appeal.…”
Section: Discussionmentioning
confidence: 99%
“…Diversification of landscapes and cropping practices have been extensively studied in recent years to strengthen sustainability within the agricultural landscape. Various studies reported its benefits for biodiversity conservation (Honnay et al, 2003;Martínez-Núñez et al, 2023;Tscharntke et al, 2021), yield regulation (Galpern et al, 2020;Nguyen et al, 2022;Reckling et al, 2022), and maintenance of ecosystem services (Rusch et al, 2016;Tamburini et al, 2020). However, because land is limited, for landscape planning one needs to address landscape multifunctionality to produce food and energy, and provide habitats and other ecosystem services.…”
Section: Discussionmentioning
confidence: 99%